2015
DOI: 10.1182/blood-2014-05-575001
|View full text |Cite
|
Sign up to set email alerts
|

Morgana acts as an oncosuppressor in chronic myeloid leukemia

Abstract: Key Points Morgana haploinsufficiency in mice causes a lethal and transplantable CML-like myeloid neoplasm. Morgana is underexpressed in aCML and in a subgroup of CMLs, where it predicts a worse response to imatinib but sensitivity to ROCK inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 50 publications
1
35
0
Order By: Relevance
“…Immunohistochemistry experiments were performed on formalin-fixed, paraffin-embedded tissues from n = 5 patients, as previously reported [60]. …”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemistry experiments were performed on formalin-fixed, paraffin-embedded tissues from n = 5 patients, as previously reported [60]. …”
Section: Methodsmentioning
confidence: 99%
“…Rho-associated coiled-coil kinases (ROCKs) are major effectors of the small GTPase RHOA, the important role of ROCK in cancer progression including cell metastasis has been demonstrated by thousands of studies (21)(22)(23). Moreover, ROCK inhibitors such as Y-27632 (24) or fasudil (25) have also been widely studied in various cancer cell lines and animal models and showed significant benefits when used along (26)(27)(28) or combined with other chemotherapy drugs (29)(30)(31). Though the role of ROCK2 in basic studies was no questioned, only one clinical trial using ROCK2 inhibitor AT13148 in cancer treatment was reported in 2012 (ClinicalTrials.gov identifier NCT01585701).…”
Section: Discussionmentioning
confidence: 99%
“…ROCKs are major effectors of the small GTPase RHOA, and the important roles of ROCK in cancer progression, including in cell metasta sis, have been demonstrated by thousands of studies (23)(24)(25). Moreover, ROCK inhibitors such as Y-27632 (26) and fasudil (27) have also been widely studied in various cancer cell lines and animal models and have shown signi cant bene ts when used alone (28)(29)(30) or in combination with other chemotherapeutic drugs (31)(32)(33). Although the role of ROCK2 shown in basic studies has not been questioned, only one clinical trial using the ROCK2 inhibi tor AT13148 for cancer treatment was reported in 2012 (ClinicalTrials.gov identi er NCT01585701).…”
Section: Discussionmentioning
confidence: 99%